2022
DOI: 10.3389/fdgth.2022.932411
|View full text |Cite
|
Sign up to set email alerts
|

An integration engineering framework for machine learning in healthcare

Abstract: Background and ObjectivesMachine Learning offers opportunities to improve patient outcomes, team performance, and reduce healthcare costs. Yet only a small fraction of all Machine Learning models for health care have been successfully integrated into the clinical space. There are no current guidelines for clinical model integration, leading to waste, unnecessary costs, patient harm, and decreases in efficiency when improperly implemented. Systems engineering is widely used in industry to achieve an integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Results: Data from 9415 patients who underwent cardiac surgery (median [IQR] age, 68 [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] years; 2554 [27.1%] women) were included. Overall mortality rates at 30 days, 1 year, and 5 years were 268 patients (2.8%), 420 patients (4.5%), and 612 patients (6.5%), respectively.…”
Section: Main Outcomes and Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Results: Data from 9415 patients who underwent cardiac surgery (median [IQR] age, 68 [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] years; 2554 [27.1%] women) were included. Overall mortality rates at 30 days, 1 year, and 5 years were 268 patients (2.8%), 420 patients (4.5%), and 612 patients (6.5%), respectively.…”
Section: Main Outcomes and Measuresmentioning
confidence: 99%
“…Integration into an already existing clinical workflow is, and will remain, the challenge faced by researchers, clinicians, and others in the implementation of decision support systems 71,72 It has been suggested that the American National Aeronautics and Space Administration (NASA) system of Technology Readiness Levels (TRLs), which assesses air-and spacecrafts "readiness to fly", could also be adopted for digital health innovations. Following this principle, clinical applications of AI-enabled decision support systems should occur only when there is adequate evidence of its safety and efficacy 70,73 .…”
Section: Supplementary Materialsmentioning
confidence: 99%